Reproductive performance of silver catfish fed sorghum diets supplemented with phytase - Rodrigues, Mariana Lins (2017)
The objective of this work was to evaluate the reproductive performance of silver catfish (Rhamdia quelen) fed diets containing sorghum, as a replacement for corn, supplemented or not with phytase. The experiment was carried out with 360 fish, with 16.02 +/- 0.58 g mean initial weight, fed diets in which low-tannin sorghum replaced corn at 0, 50, and 100%, with or without phytase supplementation (1,500 FTU per kilogram of feed). Diets supplemented with phytase or with 100% sorghum led to a reduction of visceral fat deposition and hepatic mass in males. In females, similar results were observed for diets containing phytase. Females fed sorghum-only diets, supplemented or not with phytase, had bigger oocytes. Males and females at the developing and final stages of gonadal maturation were found in all treatments. The replacement of corn by sorghum affects neither semen quality nor the fertilization rate of gametes. Therefore, complete replacement of corn with low-tannin sorghum in the diet can be performed without compromising the reproductive performance or the somatic indexes of silver catfish.